1979
DOI: 10.1136/bmj.2.6181.21
|View full text |Cite
|
Sign up to set email alerts
|

Costs of unnecessary tests.

Abstract: Summary and conclusionsThe relative importance of the history, examination, and routine and special investigations has been assessed in the diagnosis and management of 630 medical outpatients. The history was the most important factor in both diagnosis and management in cardiovascular, neurological, respiratory, urinary, and other miscellaneous problems, and decided 56% of all diagnoses and 46% of all management. Examination findings were of more limited value, accounting for only 17% of diagnostic and 17% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(36 citation statements)
references
References 2 publications
0
33
0
2
Order By: Relevance
“…23 Other studies also have demonstrated that the history and CANADIAN JOURNAL OF ANAESTHESIA physical examination accurately indicate all areas in which subsequent laboratory testing proves beneficial to patients. For example, Rabkin and Home 24'2s examined the records of 165 patients having "new" (i.e., a change from a previous tracing) abnormalities on electrocardiogram (ECG) that were potentially "surgically significant" (i.e., that might affect perioperative management or outcome).…”
Section: Routine Laborawry Testing Is Not the Most Effective Way Of Ementioning
confidence: 99%
“…23 Other studies also have demonstrated that the history and CANADIAN JOURNAL OF ANAESTHESIA physical examination accurately indicate all areas in which subsequent laboratory testing proves beneficial to patients. For example, Rabkin and Home 24'2s examined the records of 165 patients having "new" (i.e., a change from a previous tracing) abnormalities on electrocardiogram (ECG) that were potentially "surgically significant" (i.e., that might affect perioperative management or outcome).…”
Section: Routine Laborawry Testing Is Not the Most Effective Way Of Ementioning
confidence: 99%
“…. , tungssystems und Implementierung eines teil-oder Zur Vermeidung von Redundanz und Kosten bei der voUm echanisierten Verteügerätes nur unbefriedigend Bestimmung klinisch-chemischer Kenngroßen ist bei der " ^ Wefden Anforderung klinisch-chemischer Untersuchungen eine diskrimiriierte Auswahl sinnvoll (1)(2)(3)(4).…”
Section: Einführungunclassified
“…Of these three elements, good doctor-patient communica tion during the interview is of critical impor tance in diagnostic decision making [2], Thus, Hampton et al [3] reported that the final diagnosis depended on the interview in 83% of general medical outpatients, while Sandler [4] estimated approximately 56%. In contrast, physical examination contrib uted only 17% of diagnostic decisions.…”
Section: Clinical Assessmentmentioning
confidence: 99%